PENGARUH KEPMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, LINGKUNGAN KERJA DAN BUDAYA SEKOLAH TERHADAP KINERJA GURU DI KECAMATAN NISAM ANTARA - Rahmi, Rahmi; Idialita, Idialita; Marwan, Marwan; Amiruddin, Amiruddin (Universitas Islam Negeri Sumatera Utara Medan, 2022)
This study aims to examine and analyze the effect of the transformational leadership of school principals, work environment, and school culture on the performance of teachers in Nisam Antara District. This research was conducted in the Nisam Antara sub-district in November 2022. The population in this study were junior high school teachers in the Nisam Antara sub-district. The number of samples in this study amounted to 68 people from three junior high schools in Nisam Antara District. The sample in this study used a saturated sampling technique. Data was collected using multiple linear regression. The results of the analysis show that the principal's transformational leadership, the work environment and school culture together influence teacher performance. While the work environment has no effect on teacher performance. Keywords:Principal transformational leadership, work environment, school culture and teacher performance.